Nicotine receptor partial agonists for smoking cessation. - Cahill, K; Stead, L; Lancaster, T (2008)
BACKGROUND: Nicotine receptor partial agonists may help people to stop smoking by a combination of maintaining moderate levels of dopamine to counteract withdrawal symptoms (acting as an agonist) and reducing smoking satisfaction (acting as an antagonist). Varenicline was developed as a nicotine receptor partial agonist from cytisine, a drug widely used in central and eastern Europe for smoking cessation. The first trial reports of varenicline were released in 2006, and further trials have now been published or are currently are underway. OBJECTIVES: The primary objective of this review is to assess the efficacy and tolerability of nicotine receptor partial agonists, including varenicline and cytisine, for smoking cessation. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group's specialised register for trials, using the terms ('varenicline' or 'cytisine' or 'Tabex' or 'nicotine receptor partial agonist') and 'smoking' in the title or abstract, or as keywords. We also searched MEDLINE, EMBASE, PsycINFO and CINAHL using MeSH terms and free text, and we contacted authors of trial reports for additional information where necessary. The latest search was in March 2008. SELECTION CRITERIA: We included randomized controlled trials which compared the treatment drug with placebo. We also included comparisons with bupropion and nicotine patches where available. We excluded trials which did not report a minimum follow-up period of six months from start of treatment. DATA COLLECTION AND ANALYSIS: We extracted data in duplicate on the type of participants, the dose and duration of treatment, the outcome measures, the randomization procedure, concealment of allocation, and completeness of follow up. The main outcome measured was abstinence from smoking after at least six months from the beginning of treatment. We used the most rigorous definition of abstinence, and preferred biochemically validated rates where they were reported. Where appropriate we performed meta-analysis to produce a risk ratio, using the Mantel-Haenszel fixed-effect model. MAIN RESULTS: We found seven trials of varenicline compared with placebo for smoking cessation; three of these also included a bupropion experimental arm. We found one relapse prevention trial, comparing varenicline with placebo. We also found one open-label trial comparing varenicline with nicotine replacement therapy. The nine trials covered 7267 participants, 4744 of whom used varenicline. We identified one trial of cytisine (Tabex) for inclusion. The pooled risk ratio (RR) for continuous abstinence at six months or longer for varenicline versus placebo was 2.33 (95% confidence interval [CI] 1.95 to 2.80). The pooled RR for varenicline versus bupropion at one year was 1.52 (95% CI 1.22 to 1.88). The RR for varenicline versus NRT at one year was 1.31 (95% CI 1.01 to 1.71). The two trials which tested the use of varenicline beyond the 12-week standard regimen found the drug to be well-tolerated during long-term use. The main adverse effect of varenicline was nausea, which was mostly at mild to moderate levels and usually subsided over time. Post-marketing safety data suggest that varenicline may be associated with depressed mood, agitation, and suicidal behaviour or ideation. The labelling of varenicline has been amended, and the FDA is conducting a safety review. The one cytisine trial included in this review found that more participants taking cytisine stopped smoking compared with placebo at two-year follow up, with an RR of 1.61 (95% CI 1.24 to 2.08). AUTHORS' CONCLUSIONS: Varenicline increased the chances of successful long-term smoking cessation between two- and threefold compared with pharmacologically unassisted quit attempts. More participants quit successfully with varenicline than with bupropion. One open-label trial of varenicline versus nicotine replacement therapy demonstrated a modest benefit of varenicline. The effectiveness of varenicline as an aid to relapse prevention has not been clearly established. The main adverse effect of varenicline is nausea, but mostly at mild to moderate levels and tending to subside over time. Possible links with serious adverse events, including depressed mood, agitation and suicidal thoughts, are currently under review. There is a need for independent community-based trials of varenicline, to test its efficacy and safety in smokers with varying co-morbidities and risk patterns. There is a need for further trials of the efficacy of treatment extended beyond 12 weeks. Cytisine may also increase the chances of quitting, but the evidence at present is inconclusive.